Comparison Of Liver Cell Models Using The Basel Phenotyping Cocktail - Berger, Benjamin; Donzelli, Massimiliano; Maseneni, Swarna; Boess, Franziska; Roth, Adrian; Krähenbühl, Stephan; Haschke, Manuel (Frontiers in Pharmacology, 2016)
Currently used hepatocyte cell systems for in vitro assessment of drug metabolism include hepatoma cell lines and primary human hepatocyte (PHH) cultures. We investigated the suit-ability of the validated in vivo Basel phenotyping cocktail (caffeine [CYP1A2], efavirenz [CYP2B6], losartan [CYP2C9], omeprazole [CYP2C19], metoprolol [CYP2D6], midazolam [CYP3A4]) in vitro and characterized four hepatocyte cell systems (HepG2 cells, HepaRG cells, and primary cryopreserved human hepatocytes in 2-dimensional [2D] culture or in 3D-spheroid co-culture) regarding basal metabolism and CYP inducibility. Under non-induced conditions, all CYP activities could be determined in 3D-PHH, CYP2B6, CYP2C19, CYP2D6 and CYP3A4 in 2D-PHH and HepaRG, and CYP2C19 and CYP3A4 in HepG2 cells. The highest non-induced CYP activities were observed in 3D-PHH and HepaRG cells. mRNA expression was at least 4-fold higher for all CYPs in 3D-PHH compared to the other cell systems. After treatment with 20µM rifampicin, mRNA increased 3 to 50-fold for all CYPs except CYP1A2 and 2D6 for HepaRG and 3D-PHH, 4-fold (CYP2B6) and 17-fold (CYP3A4) for 2D-PHH and 4-fold (CYP3A4) for HepG2. In 3D-PHH at least a 2-fold in-crease in CYP activity was observed for all inducible CYP isoforms while CYP1A2 and CYP2C9 activity did not increase in 2D-PHH and HepaRG. CYP inducibility assessed in vivo using the same phenotyping probes was also best reflected by the 3D-PHH model. Our studies show that 3D-PHH and (with some limitations) HepaRG are suitable cell systems for assessing drug metabolism and CYP induction in vitro. HepG2 cells are less suited to as-sess CYP induction of the 2C and 3A family. The Basel phenotyping cocktail is suitable for the assessment of CYP activity and induction also in vitro.